Kesadaran Orang Tua dan Lingkungan Belajar dalam Motivasi Belajar Siswa SDN Sukolilo 250 Surabaya - Fauziyah, Dhea (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2025)
This study explains about parental awareness and learning environment in the learning motivation of students at SDN Sukolilo 250 Surabaya and aims to explain the influence of parental awareness (X1) and learning environment (X2) in the learning motivation (Y) of students at SDN Sukolilo 250 Surabaya and explain the influence of student learning motivation strengthened by the student learning environment. The analysis method uses Travis Hirschi's social control theory. In this study, the author used quantitative research with an explanatory research type and used 3 variables including parental awareness, learning environment and student motivation. The results of the study are (1). The influence of parental awareness (X1) with learning motivation (Y) shows a significance value found of 0.138, (2) the variable learning environment (X2) with learning motivation (Y) shows a significance value found of 0.021 and (3) The influence of parental awareness (X1) and learning environment (X2) with learning motivation (Y) shows a significance value found of 0.000. The analysis used is data processing, validity and reliability testing, and hypothesis testing.